Integrative strategy formation process and the management of complex work - a microorganizational analisys - Rosalia Aldraci Barbosa Lavarda; Maria Teresa Canet-Giner; Fernando Juan Peris-Bonet (BBR: Brazilian Business Review)
The goal of this study is to analyse how the strategy formation process takes place; studying the relevance of the integrative perspective and the use of the variables rationality, involvement and vision; Verifying the relationship between an integrative strategy formation process and the management of work and the consequences of this relationship in terms of performance, identifying the causes for a better fit; Also, verify the propositions that have been formulated and looking for new variables that could affect the relationship between strategic process and work management. It has been adopted a qualitative methodology through a study case. After the case analysis it has been identified two different variables (flexibility and the role of the middle manager) that can have an influence in the subject of study; also, it has been found that if there is an important fit between the variables that define an integrative strategy formation process and the design variables used in the management of work, the process will be more efficient and, consequently, the organisation will obtain better results.